Diversidade cultural, bilinguismo e política linguística em discuros escolares indígenas do Estado do Paraná : a identidade em governamentalidade - Liss, Margarida (2011)
Assuming that societies are organized in the power/knowledge relations, the identities included in social organizations are under immediate coercions of governmentalization, once governmentality establishes model practices of conduct. Concerning indigenous subjects, such process is evidenced by specific devices, especially in the scholar instance, where it is frequent the presence of bilingual text books, founded on the one hand by the Cultural Diversity principles and on the other hand by the rules which govern educational practices in any school in the country, indigenous or not. Because there are specific parameters materialized in linguistic policies which guide the teaching of indigenous and Portuguese languages, there are also particular conducts institutionalized for a bilingual identity and such politics, bringing up the mechanisms that promote history and memory, determine, in the discursive instance, identities for the subjects. Thus, in order to provide input to the project "Evaluating socio-educational, language and bilingualism in the schools of the territory Indigenous Kaingang etnoeducacional - Brazilian Southern Plateau", sponsored by the Coordination of Improvement of Higher Education, in this dissertative work, it was investigated how the bilingualism, founded under the aegis of the Cultural Diversity at the interfaces of language with culture and memory, establishes the contradiction that curtail the social and political role of the indigenous language in the National Curriculum for indigenous schools and in text books used in indigenous educational institutions of Paraná, and produces interventions in the linguistic identity formation of the indigenous subject. In order to do so, the study was based on the methodological and theoretical principles of French Discourse Analysis, in particular, on Michael Foucault incursions in studies about the discourse, the statement and governmentality, on Cultural Studies, Linguistic Studies, Image Theories and Historiography. The results showed that the Indigenous Languages act like disciplinarization element of social and political conduct for the indigenous subjects and the languages are segregated from the National territory, which constitutes a non-place for them. It is concluded that the discursive contradiction is constitutive of linguistic policies in the contemporaneity, to the extent that the inclusion takes place under conditions regulated by the state, whose proposals delimit inclusion of the language in a territory and the exclusion of another one. So the linguistic policy rules not only the determination as to which geographical space can an indigenous language occupy, but also the manner and circumstances in which it can be used, such as being the oral instruction language for contents related to indigenous culture. Therefore, a linguistic identity is promoted split between local and national once it is the Portuguese Language that, besides being used in indigenous territories, allows the exercise of legal rights, economic transactions, in short, the exercise of citizenship while indigenous language is unable to transcend the limits established. So when promoting the territorialization of the language and its delimitation of functions, the restriction of bilingualism and Cultural Diversity promotion happens.